Shoot regeneration of limau purut (Citrus hystrix) using shoot tip: assessment of calcium gluconate and silver nitrate in overcoming premature leaf senescence - Eng, Wee Hiang; Abdul Aziz, Maheran; Sinniah, Uma Rani (Pakistan Botanical Society, 2014)
This study was carried out to establish an optimum In vitro shoot multiplication system using shoot tip explants derived from 7 week-old seedlings of Citrus hystrix. In the first experiment, shoot tips were cultured on Murashige & Skoog (MS) medium supplemented with 0-13.33 µM 6-benzylaminopurine (BAP) for 8 weeks. Shoot tips cultured on 2.22 µM BAP produced the highest mean number of shoots (3.42 shoots) but the shoots had low number of leaves (1.14 leaves) due to the occurrence of premature leaf senescence and callus formation. Meanwhile, the medium devoid of BAP produced the lowest mean number of shoots (1.50 shoots) but highest mean number of leaves (5.41 leaves) indicating that BAP was likely responsible for the premature leaf senescence. In order to overcome the occurrence of premature leaf senescence on medium with BAP, a second experiment was carried out whereby shoot tips were cultured on medium containing 2.22µM BAP fortified with 2.00, 4.00 and 6.00 mM calcium gluconate (Ca-glu) and a control treatment with 2.22 µM BAP. The shoot and leaf numbers were increased with the addition of 4.00 and 6.00 mM Ca-glu. The presence of Ca-glu reduced premature leaf senescence and callus formation to some extent. In the third experiment, the addition of silver nitrate (AgNO3) at 10–80 µM in media with 2.22 µM BAP and 2.22 µM BAP + 4 mM Ca-glu could totally overcome premature leaf senescence and callus formation. Media supplemented with 2.22 µM BAP + 4 mM Ca-glu + 20 µM AgNO3 significantly induced among the highest mean number of shoots and highest mean number of leaves per shoot.